IL-17 and Disease Activity in Spondyloarthitis - , Yuliasih; Lanasakti, Yusdeny (Folia Medica Indonesiana, 2021)
Highlight: • The correlation of IL-17 to disease activity by The Ankylosing Spondylitis Disease Activity Score C-Reactive Protein (ASDAS-CRP) was identified. • IL-17 level is strongly correlated to disease activity in SpA patients. Abstract: IL-17 is a new cytokine involved in the pathogenesis of Spondyloarthritis (SpA). Recent studies show that IL-17 level correlates to disease activity, and it is used as a basis in treating SpA patients who do not respond to anti-TNF-α. This study identified the correlation of IL-17 to disease activity measured by The Ankylosing Spondylitis Disease Activity Score C-Reactive Protein (ASDAS-CRP). This study was a cross-sectional study involving SpA patients according to the 2009 ASAS criteria in Dr. Soetomo General Academic Hospital, Surabaya. Disease activity and IL-17 level were analyzed using Spearman correlation test to see the strength of correlation. Forty SpA patients showed mean age of 53.58 ± 9.28 years with a body mass index of 24.36 ± 3.23 kg/m2, ESR of 39.50 ± 18.76 mm/hour, clinically obtained Schober Test of 13.11 ± 1.22 cm, chest extension test of 1.45 ± 0.77 cm, and tragus-to-wall test 13.53 ± 1.99 cm. The median CRP and IL-17 were 0.3 (0.10-5.70) mg/dL and 9.30 (7.70-13.60) pg/dL, respectively. Based on the ASDAS-CRP system, the patients showed disease activities that fall into the category was high (62.5%), moderate (35%), and inactivity (2.5%). IL-17 level is strongly correlated to disease activity in SpA patients (p=0.000, r = 0.711).